2009
DOI: 10.1149/1.3098499
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Catalyst Layer Binder on Catalyst Utilization and Performance of Fuel Cell with Polybenzimidazole-H[sub 3]PO[sub 4] Membrane

Abstract: This article reports on the impact of the catalyst layer (CL) binder on the performance of fuel cell (FC) with normalH3PnormalO4 -doped polybenzimidazole membrane. Nafion and fluorinated ethylenepropylene (FEP) were used as binders for carbon-supported platinum catalyst. FC performance declined with the increase of binder concentration in CL. Nafion binder was found to be more detrimental to FC performance than FEP. Changes of platinum electrochemically active surface area (ESA) in the cathode were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…These results are based on studies of adsorption and electrochemical oxidation of CO in concentrated phosphoric acid in different catalytic systems, in the presence of water vapor. At a temperature of 180°C with a pure H 2 feed, and a voltage on the membrane electrode assembly (MEA) of 0.6 V, the discharge current density is 0.5 A/cm 2 , which matches the characteristics for BASF, the world leader in the area of this type of fuel cell [5]. When feeding hydrogen fuel containing 10% CO, the voltage decreases only by 30-40 mV, and the current density at 0.6 V was 0.4 A/cm 2 (Fig.…”
mentioning
confidence: 59%
“…These results are based on studies of adsorption and electrochemical oxidation of CO in concentrated phosphoric acid in different catalytic systems, in the presence of water vapor. At a temperature of 180°C with a pure H 2 feed, and a voltage on the membrane electrode assembly (MEA) of 0.6 V, the discharge current density is 0.5 A/cm 2 , which matches the characteristics for BASF, the world leader in the area of this type of fuel cell [5]. When feeding hydrogen fuel containing 10% CO, the voltage decreases only by 30-40 mV, and the current density at 0.6 V was 0.4 A/cm 2 (Fig.…”
mentioning
confidence: 59%
“…In some anhydrous PEMs, phosphoric acid acted quite effectively as the proton source and solvent upon being doped in azole-functional polymer matrices [34][35][36][37][38]. At temperatures above 150°C, the humidity gets low and the proton conductivities are typically high.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that the structure and composition of the gas diffusion electrode (GDE) has to be compatible with a membrane used as a polymer electrolyte. Whereas significant attention has been paid in the past to the optimization of the GDE for the classical PEM fuel cell utilizing a PFSA membrane, reviewed by Wee et al [9], scarcely any systematic studies have been published on the optimization of the GDE for a PEM fuel cell based on phosphoric acid-doped PBI [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Modestov et al [14] investigated the utilization of Nafion and fluorinated ethylenepropylene (FEP) as a CL binder. He found that the first polymer had a detrimental effect on the performance of this type of fuel cell.…”
Section: Introductionmentioning
confidence: 99%